2017
DOI: 10.1177/1362361317699586
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of driver licensing rates among adolescents and young adults with autism spectrum disorder

Abstract: Driving may increase mobility and independence for adolescents with autism without intellectual disability (autism spectrum disorder); however, little is known about rates of licensure. To compare the proportion of adolescents with and without autism spectrum disorder who acquire a learner's permit and driver's license, as well as the rate at which they progress through the licensing system, we conducted a retrospective cohort study of 52,172 New Jersey residents born in the years 1987-1995 who were patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 29 publications
5
27
0
Order By: Relevance
“…When specific methodologies and procedures are in place to support young persons with ASD, this could also enhance the number of positive decisions concerning the pursuit of a driving licence. At present, research suggests that there may be an important discrepancy between a strong interest in driving and relatively lower licensure rates among adolescents with ASD (Curry et al, 2017).…”
Section: Adjustments To the Driving Lessonsmentioning
confidence: 93%
See 2 more Smart Citations
“…When specific methodologies and procedures are in place to support young persons with ASD, this could also enhance the number of positive decisions concerning the pursuit of a driving licence. At present, research suggests that there may be an important discrepancy between a strong interest in driving and relatively lower licensure rates among adolescents with ASD (Curry et al, 2017).…”
Section: Adjustments To the Driving Lessonsmentioning
confidence: 93%
“…At this point, intervention by a trained instructor is required in order to stop driving and refocus on the task through appropriate methods (Tyler, 2013). In summary, pupils with ASD will generally take longer to complete driving training (also observed by Curry et al, 2017) because they need to learn coping strategies and develop social communication skills on top of driving skills. It is necessary to teach pupils with ASD all the road regulations, gestures and courtesies in driving; even the ones not listed in the books, which neurotypical drivers may understand more easily.…”
Section: Asd and Learning How To Drivementioning
confidence: 99%
See 1 more Smart Citation
“…25 A recent study that linked 52,000 electronic health records of children born from 1987 to 1995 and New Jersey driver licensing data found that about one-third of people with autism were able to obtain a driver's license. 26 Another study, which surveyed adults (online convenience sample of 703) with autism through various autism-related organizations in New Jersey (or 2016 New Jersey survey), found that 9.3% of respondents had a driver's license. 27 An earlier study by Feeley (or 2010 Feeley et al survey), which surveyed adults with autism or their parent or caretakers (an online convenience sample of 1,077 with recruitment focused in New Jersey) reported that 24.3% of respondents, many of whom identified as higher-functioning, said that they primarily drove themselves to activities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates suggest that roughly one third of individuals with ASD currently drive (Curry et al 2017), although Cox et al (2012) found that 48% of surveyed parents of a child with ASD reported that their child had successfully attained a driver’s license. Huang et al (2012) found that 30% of age-eligible individuals with ASD do drive, and another 34% plan to do so.…”
Section: Introductionmentioning
confidence: 99%